Digital transformation of work: spillover effects of workplace innovation on social innovation - Dhondt, Steven (Elgar Research Agendas, 2021)
In becoming socially active in their daily lives, citizens may be impacted by their daily work settings. How their work explains the social participation of citizens, however, needs to be better understood. Workplace democracy and active work settings - elements of workplace innovation - are relevant to stimulate citizens to become more active and is therefore relevant for social innovation. Digital technologies have profound impacts on work settings, as well in positive as in negative sense. The digital transformation needs to be better understood to see how it can help this active citizen. This chapter develops core ideas for a social innovation research agenda, starting from the future workplaces.